Recent developments in the identification and biosynthesis of antitumor drugs derived from microorganisms - Qi Gao; Sizhe Deng; Tianyu Jiang (Engineering Microbiology, 2022)
Secondary metabolites in microorganisms represent a resource for drug discovery and development. In particular, microbial-derived antitumor agents are in clinical use worldwide. Herein, we provide an overview of the development of classical antitumor drugs derived from microorganisms. Currently used drugs and drug candidates are comprehensively described in terms of pharmacological activities, mechanisms of action, microbial sources, and biosynthesis. We further discuss recent studies that have demonstrated the utility of gene-editing technologies and synthetic biology tools for the identification of new gene clusters, expansion of natural products, and elucidation of biosynthetic pathways. This review summarizes recent progress in the discovery and development of microbial-derived anticancer compounds with emphasis on biosynthesis.